SAT0388 Long-Term Efficacy and Tolerability of Golimumab in Active Nonradiographic Axial Spondyloarthritis: Results of The Open-Label Extension of A Randomized, Double-Blind Study. (15th July 2016) - van der Heijde, D.; Dougados, M.; Maksymowych, W.P.; Braun, J.; Bergman, G.; Curtis, S.P.; Tzontcheva, A.; Philip, G.; Huyck, S.; Sieper, J.
Abstract : Background: The efficacy and tolerability of golimumab (GLM) for nonradiographic axial spondyloarthritis (nr-axSpA) have been demonstrated in a 16-week randomized, double-blind (DB), placebo (PBO)-controlled, phase 3 study (GO-AHEAD; NCT01453725 ). 1 Objectives: We report the long-term results from an open-label extension (OLE) of GO-AHEAD. Methods: Patients (pts) completing the 16-week DB study (GLM or PBO) received open-label GLM 50 mg every 4 weeks (36-week efficacy period; 8-week safety follow-up). Prespecified responder analyses for ASAS20, ASAS40, BASDAI50, and ASAS partial remission (PR) at weeks 16, 20, 24, 32, 40, and 52 used the OLE-treated population (GLM/GLM, n=93; PBO/GLM, n=96). In a post hoc analysis, the DB-treated population was used for GLM/GLM responder analyses (GLM/GLM, n=97). Non-responder imputation was used for missing ASAS20, ASAS40, and ASAS PR values; LOCF imputation was used for missing BASDAI data. The incidence/severity of adverse events (AEs) were recorded. Data were summarized descriptively. Results: In total, 176/189 (93%) pts entering the OLE completed week 60 (GLM/GLM, 85/93 [91%]; PBO/GLM, 89/96 [93%]). In the prespecified analysis, the proportions of ASAS20, ASAS40, BASDAI50, and ASAS PR responders in the OLE were similar to those in the DB phase among pts who continued GLM (GLM/GLM group); consistent results were observed in the GLM/GLM group when using the DB-treated population (Figure A, B ). Among pts who switched from PBO in the DB phase to GLM in the OLE (PBO/GLM group), there were higher proportions of responders to GLM in the OLE than responders to PBO in the DB phase (Figure C ). There were no notable differences in the number/types of AEs between the GLM/GLM and PBO/GLM groups (Table ). Conclusions: In the GO-AHEAD OLE, improvements in disease activity were retained in pts who received GLM and in pts who switched from PBO to GLM. Consistent with results of the GO-AHEAD DB study, treatment with GLM in the OLE was generally well tolerated in pts with nr-axSpA. References: Sieper J, et al. Arthritis Rheum. 2015;67(10), 2702–2712. Disclosure of Interest: D. van der Heijde Consultant for: AbbVie, Amgen, AstraZeneca, Augurex, BMS, Boehringer Ingelheim, Celgene, Centocor, Chugai, Covagen, Daiichi, Eli-Lilly, Galapagos, GSK, Janssen Biologics, Merck, Novartis, Novo-Nordisk, Otsuka, Pfizer, Roche, Sanofi-Aventis, UCB, Vertex, Employee of: Imaging Rheumatology BV, M. Dougados Grant/research support from: AbbVie, Lilly, Novartis, Pfizer, Roche, Sanofi, UCB, W. Maksymowych Grant/research support from: AbbVie, Janssen, Pfizer, Consultant for: AbbVie, Amgen, UCB, Pfizer, Merck, Janssen, Eli Lilly, Celgene, Synarc, Boehringer, J. Braun Grant/research support from: Abbvie (Abbott), Amgen, Biogen, Boehringer, BMS, Celgene, Celltrion, Centocor, Chugai, EBEWE Pharma, Epirus, Hospira, Janssen, Medac, MSD (Schering-Plough), Mundipharma, Novartis, Pfizer (Wyeth), Roche, Sanofi-Aventis and UCB, Consultant for: Abbvie (Abbott), Amgen, Biogen, Boehringer, BMS, Celgene, Celltrion, Centocor, Chugai, EBEWE Pharma, Epirus, Hospira, Janssen, Medac, MSD (Schering-Plough), Mundipharma, Novartis, Pfizer (Wyeth), Roche, Sanofi-Aventis and UCB, G. Bergman Shareholder of: Merck & Co., Inc., Kenilworth, NJ, USA, Employee of: Merck & Co., Inc., Kenilworth, NJ, USA, S. Curtis Shareholder of: Merck & Co., Inc., Kenilworth, NJ, USA, Employee of: Merck & Co., Inc., Kenilworth, NJ, USA, A. Tzontcheva Shareholder of: Merck & Co., Inc., Kenilworth, NJ, USA, Employee of: Merck & Co., Inc., Kenilworth, NJ, USA, G. Philip Shareholder of: Merck & Co., Inc., Kenilworth, NJ, USA, Employee of: Merck & Co., Inc., Kenilworth, NJ, USA, S. Huyck Shareholder of: Merck & Co., Inc., Kenilworth, NJ, USA, Employee of: Merck & Co., Inc., Kenilworth, NJ, USA, J. Sieper Consultant for: AbbVie, Eli Lilly, Janssen Biologics, Merck, Novartis, Pfizer, Roche, UCB